The Impact of Gamification on Sales Performance: A New Approach to Increasing Sales Volume (Journal of Information Technology and Digital World, 2025)
This article analyses the influence of gamification on sales performance based on case study findings and psychological theory. Based on Skinner's Reinforcement Theory and Festinger's Social Comparison Theory, a conceptual model is developed to study the effect of gamified elements (points, leaderboards, rewards, and challenges) on the extrinsic and intrinsic motivation of the salesforce. In particular, Reinforcement Theory is summarized in how rewards, points, and badges encourage repeated selling behavior, and Social Comparison Theory is leveraged by leaderboards and peer-to-peer comparison that foster healthy competition and accountability. The study effectively cross-references psychological drivers of autonomy, flow, and reinforcement with key sales performance indicators that are significant and measurable such as engagement levels, conversion rates, and quota attainment. Experiments have proven that gamification can improve motivation, engagement and learning ability, decision-making, and long-term goal achievement. The second case study limitation is the misuse of data and overdependence on extrinsic motivation. The study adds to the literature by demonstrating a compelling systematic translation of gamification theory and sales KPIs into theory development and practice.
Keywords: Gamification; Sales Performance; Rewards; Motivation; Competition